Implementasi Pembelajaran Bermakna (Deep Learning) Melalui Media Digital Untuk Menstimulasi Literasi Sains Anak Usia 4-5 Tahun - Ismiatun; Nurul Ismaiyah; Aisyah Ghazi; Aisyatul Wildat; Rini Tiana (E-JURNAL AKSIOMA AL-ASAS, 2026)
This study aims to describe the implementation of meaningful leaning through digital media in stimulating science literacy among 4-5 year-old children at RA Al Munawwarah. The study cmployed lescriptive-interpretative qualitative approach conducted over four weeks involving 15 children. Data were collected through participant observation, semi-structured interviews, and docamentation. The results indicate that digital media serve as an initial visual stimulus that enhances children's attention and aids in the formation of conceptual representations prior to their engaging in direct exploratory activities. The integration of digital stimuli with concrete experiences consistently elicited indicators of science literacy, particularly in the abilities to observe and experiment, with a significant improvement in the ability to communicate observational findings by the fourth week. These findings confirm that the effectiveness of digital media in early childhood science leaming does not lie in its isolated use, but rather in its ructured integration with exploratory activities. This study contributes to the understanding of the role of digital media as pedagogical scaffolding in supporting meaningful and sustainable science learning in carly chiklhood education.